Buy It Now : Lessons from eBay - White, Michele, 1962- (Book collections on Project MUSE., 2012)
In Buy It Now, Michele White examines eBay and its emphasis on community and social norms, revealing the cultural assumptions about gender, race, and sexuality that are reinforced throughout the site. She shows how instructional texts, rule systems, and advertisements ""configure the user, "" allowing eBay to indicate how the site is supposed to function while concurrently upholding and promoting particular social values, practices, and norms.